Two new species of jellyfishes (Cnidaria: Cubozoa: Carybdeida) from tropical Western Australia, presumed to cause Irukandji Syndrome - Gershwin, Lisa-Ann (Zootaxa, 2005)
Two new jellyfishes are described from the waters off northwestern Australia. The first, Carukia shinju n. sp., is similar to the common Queensland Irukandji Carukia barnesi, but differs from the latter in having a larger body size, branched velarial canals, nematocyst warts on both the velarial canals and the perradial lappets, fully-spined tentacular nematocyst shafts, about 14 naked ringlets between adjacent tentacular nematocyst bands, and long, narrow, capitate rhopaliar horns. The second, Malo maxima n. gen. n. sp., is distinctive from other known cubozoan species by its unique combination of having a tall, narrow, robust body with a flattened apex; frown-shaped rhopaliar niche ostia; short, broad, straight rhopaliar horns; small, narrow pedalia with a single row of nematocyst patches on the outer keel and fine, cylindrical unmodified tentacles; moderately developed perradial mesenteries; 4 simple to bifurcated velarial canals per octant arising from a single base; and lacking both gastric phacellae and a thorn-like diverticulum of the pedalial canals. Both species are thought to be dangerous to humans, causing Irukandji syndrome.